2015
DOI: 10.5603/ep.2015.0036
|View full text |Cite
|
Sign up to set email alerts
|

Niedoczynność tarczycy u pacjentów z zespołem metabolicznym

Abstract: Introduction: Metabolic syndrome involves abdominal obesity, arterial hypertension, type 2 diabetes and lipid disorders manifested as atherogenic dyslipidaemia. Abnormal thyroid function affects the severity of MetS components, since regulating metabolism is one of the most important functions of thyroid hormones. In this study, we present the influence of hypothyroidism on lipid and carbohydrate disorders in patients with MetS. Material and methods: The described study was a prospective, two-centre screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
1
4
0
1
Order By: Relevance
“…In this sense, it has been reported that small variations in TSH levels, caused by minimal changes in T4 dosage during replacement therapy in hypothyroid patients, are associated with significant changes in resting energy expenditure. These observations support the clinical evidence that hypothyroidism represents a risk factor for the development of overweight and obesity [51,53].…”
Section: Thyroid Dysfunction and Obesitysupporting
confidence: 89%
“…In this sense, it has been reported that small variations in TSH levels, caused by minimal changes in T4 dosage during replacement therapy in hypothyroid patients, are associated with significant changes in resting energy expenditure. These observations support the clinical evidence that hypothyroidism represents a risk factor for the development of overweight and obesity [51,53].…”
Section: Thyroid Dysfunction and Obesitysupporting
confidence: 89%
“…A previous study showed signs of subclinical hypothyroidism in patients with chronic schizophrenia [ 25 ], which contributes to an increase in cholesterol and blood pressure [ 40 ]. Associations were found between thyroid dysfunction and cardiovascular risk factors, and the development of MetS [ 41 ], as well as between TSH levels and the presence of MetS in patients with schizophrenia [ 42 ], and similarly in the general population [ 43 ]; therefore, it is necessary to monitor the levels of TSH and THs in patients with schizophrenia as possible risk factors for developing MetS.…”
Section: Discussionmentioning
confidence: 99%
“…Second, thyroid hormones can regulate lipid metabolism in the liver via thyroid hormone receptor β, and they can decrease cholesterol and triglyceride levels ( 58 60 ). It is worth mentioning that lower levels of thyroid hormones in hypothyroidism can increase the levels of cholesterol, low-density lipoproteins and triglyceride due to the delivery of hepatic fatty acids, but decrease the level of high-density lipoprotein (HDL), and thus can affect lipid metabolism ( 61 ). Therefore, patients with overt hypothyroidism often have fatty infiltration of the liver and thus have a higher risk for NAFLD ( 47 ).…”
Section: Discussionmentioning
confidence: 99%